Inflammatory markers following resuscitation from out-of-hospital cardiac arrest—A prospective multicenter observational study. (June 2016) - Peberdy, Mary Ann; Andersen, Lars W.; Abbate, Antonio; Thacker, Leroy R.; Gaieski, David; Abella, Benjamin S.; Grossestreuer, Anne V.; Rittenberger, Jon C.; Clore, John; Ornato, Joseph; Cocchi, Michael N.; Callaway, Clifton; et al.
Abstract: Aim: The post-cardiac arrest syndrome is a complex set of pathophysiological processes including a systemic inflammatory response. The goal of the current investigation was to test the hypothesis that early inflammatory markers are independently associated with in-hospital mortality and poor neurological outcome in patients initially resuscitated from out-of-hospital cardiac arrest. Methods: This was a preplanned analysis of data collected from a prospective observational multicenter study in adult out-of-hospital cardiac arrest patients. Blood was drawn at baseline, 12 and 24 h after return of spontaneous circulation and plasma levels of interleukin (IL)-1β, IL-1 receptor antagonist (IL-1Ra), IL-6, IL-8, IL-10 and tumor necrosis factor (TNF)-α were measured. The primary outcome measure was survival to hospital discharge. We utilized a mixed linear model to compare the levels of cytokines in survivors and non-survivors over time. We used multivariable logistic regression to assess the association between IL-6 levels and mortality. Results: A total of 102 patients were analyzed. Non-survivors and patients with poor functional outcome had statistical significant higher IL-1Ra, IL-6, IL-8, and IL-10 levels (all p < 0.001) at all time points (0, 12 and 24 h) compared to survivors. Baseline IL-6 levels were a good predictor of mortality (AUC = 0.83 [95%CI: 0.75–0.92]). Baseline IL-6 levels were strongly associated with mortality in multivariable analysis (OR: 2.58 [95%CI: 1.93–3.45], p < 0.001) but were not associated with neurological outcome in multivariable analysis (OR: 1.33 [95%CI: 0.62–2.86], p = 0.47). Conclusion: Early inflammatory markers, especially IL-6, are higher in patients with a poor outcome after OHCA. IL-6 remained associated with mortality, but not functional outcome, in multivariable analysis adjusting for patient and event characteristics .